Recent Developments in Graphene-Based Membranes Structure, Mass-Transport Mechanism and Potential Applications - Sun, Pengzhan (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.